1999
DOI: 10.1242/jeb.202.13.1725
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of flap-bounding flight in the zebra finch over a wide range of speeds

Abstract: It has been proposed elsewhere that flap-bounding, an intermittent flight style consisting of flapping phases interspersed with flexed-wing bounds, should offer no savings in average mechanical power relative to continuous flapping unless a bird flies 1.2 times faster than its maximum range speed (Vmr). Why do some species use intermittent bounds at speeds slower than 1.2Vmr? The ‘fixed-gear hypothesis’ suggests that flap-bounding is used to vary mean power output in small birds that are otherwise constrained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Additionally, Wester (2014) compiled available information concerning sunbird and honeyeater foraging behavior, and the results indicated that 46 species of sunbirds and 15 species of honeyeater displayed hovering behavior while feeding. Similar to other passerines (Norberg 1975, Tobalske et al 1999), sunbirds were seen hovering usually for several seconds. The longest reported hovering performance of a sunbird ( N. famosa ) lasted for approximately 30 s (Geerts and Pauw 2009).…”
Section: Introductionsupporting
confidence: 63%
“…Additionally, Wester (2014) compiled available information concerning sunbird and honeyeater foraging behavior, and the results indicated that 46 species of sunbirds and 15 species of honeyeater displayed hovering behavior while feeding. Similar to other passerines (Norberg 1975, Tobalske et al 1999), sunbirds were seen hovering usually for several seconds. The longest reported hovering performance of a sunbird ( N. famosa ) lasted for approximately 30 s (Geerts and Pauw 2009).…”
Section: Introductionsupporting
confidence: 63%
“…During captivity, birds were individually housed in 1 m × 1 m × 1 m flight cages with ad libitum access to food and water in the form of Nektar-Plus (NEKTON ® ; Günter Enderle, Pforzheim, Baden-Württemberg, Germany) or a 20% sucrose solution. The morphology of the birds was measured using techniques described in Tobalske et al [ 31 ]. To calculate average wing chord (mm), the wing area was divided by wingspan.…”
Section: Methodsmentioning
confidence: 99%
“…We measured wing and body kinematics during descent from a platform to the ground to assess flapping-flight performance. We used wingbeat frequency, amplitude and angular velocity as power output indicators [17,38,39]; vertical and horizontal acceleration, descent angle and descent velocity as flight performance metrics; and bilateral kinematic asymmetries as indices of control [40]. We predicted that progressive increases in wing loading due to feather clipping would cause birds to compensate with their wing motions to accomplish similar body trajectories.…”
Section: Introductionmentioning
confidence: 99%